IN-VIVO IMMUNOMODULATORY ACTIVITY OF ETHANOLIC EXTRACTS OF AERIAL PARTS OF PHYLLANTHUS AMARUS PLANT IN CYCLOPHOSPHAMIDE INDUCED MICE - Hachhe, Veershetty; M, Siddaiah (Journal of Biomedical and Pharmaceutical Research, 2021)
Objective: To evaluate the immunomodulatory activity of ethanolic extract of aerial parts of phyllanthus amarus plant in cyclophosphamide induced mice. Materials and Method: To evaluate the immunomodulatory activity of ethanolic extracts of Aerial parts of phyllanthus amarus plant. on cyclophosphamide induced immunosuppression in mice. ethanolic extracts of aerial parts of phyllanthus amarus plant, (500mg/kg p.o.) were administered 13 days to albino mice and cyclophosphamide (30mg/kg i.p.) was administered on 11th,12th and 13th days 1 hour after the administration of the respective treatment. On the 14th day blood was collected by retro orbital puncture and the activity was evaluated by determining the RBC, Hb%, Platelet, total WBC and differential counts. Ethanolic extracts of aerial parts phyllantus amarus plant. showed very significant (p<0.001) counteracting effect to cyclophosphamide induced reduction in total WBC, DLC and platelet counts & significant (P<0.01) effect to that of reduction in RBC counts and Hb %. The significant inmmunostimulant effect of the ethanolic extracts of aerial parts of phyllanthus amarus plant on cyclophosphamide induced myelosuppression may be attributed towards the collective presence of saponins, sterols and tannins in the extracts, which suggest the immunomodulatory activities of the ethanolic extracts of phyllanthusamarus plant, leaves,stem and fruits. Results: The results of the study revealed the dose dependent effect of theextracts in counteracting the myelosuppression induced by cyclophosphamide as inducated by increase in RBC total WBC platelet counts, Hb% and DLC in the extract treated group (III &IV), when compared to cyclophoshamide treated group (Group II). Conclusion: Ethanolic extract of phyllanthus amarus would contribute for significant immunostimulating activity of In-Vivo Keywords: Phyllanthus amarus, Cyclophosphamide, Immunomodulatory, Myelosuppression